Uncovering the Potential of Ethylene Inhibitors on Delaying Ethylene Mediated Senescence and Preserving Cut Life of Climacteric Flowers (Journal of Agriculture and Veterinary Science, 2025)
Maintaining the vase life and quality of cut flowers is one of the main obstacle in floriculture industry. Cut flowers, especially climacteric ones have very short life span attributed due to outburst of respiration and ethylene synthesis during senescence. This increase is related to autocatalytic reaction in which exogenous ethylene initiate biosynthesis of endogenous ethylene, activating enzymes and genes involved in ethylene synthesis. Ethylene causes petal wilting and abscission, leaf yellowing and abrupt or premature death of flowers. Flower senescence in ethylene synthesis flowers can’t be eliminated but can be delayed using by application of ethylene inhibitors. Ethylene inhibitors (biosynthesis and action) can minimize the premature flower senescence in response to endogenous ethylene production. Application of these inhibitors as pulsing or holding solution reduced ethylene biosynthesis by inhibiting enzymes activities or used antagonistic molecules to bind with ethylene receptors thus inhibiting downstream signaling. This review sheds light on ethylene inhibitors types, mode of action, impact on vase life and quality of cut flowers and their limitations. This comprehensive write-up will not only help the florists, but it will provide combined and detailed information to researchers in designing their research studies.